The IAAF Rules on Testosterone Levels and the Right to Health - Mphidi, Tebogo M; Lubaale, Emma Charlene (Obiter, 2020)
The International Association of Athletics Federation (IAAF) regulates the participation of athletes, both male and female, at an international level (see IAAF website https://www.iaaf.org/home). Therefore, it has the mandate to develop criteria for the administration of athletic competitions. In pursuance of this role, in 2018, the IAAF rolled out the Eligibility Regulations for Female Classifications – Athletes with Differences in Sex Development (2018). The IAAF states that the Rules are intended to ensure that females are given the same opportunities in terms of competing in races (International Association of Athletics Federations, 2018 Eligibility Regulations for Female Classification – Athletes with Differences in Sexual Development for events from 400 metres to the mile, including 400 metres, hurdles races, 800 metres, 1500 metres, one mile races and combined events over the same distances, 26 April 2018 - the 2018 Regulations). According to these Regulations, for Relevant Athletes to be eligible to compete internationally in the 400 metres, 800 metres, and 1500 metres races, their testosterone levels have to be under 5 nanomoles (nml) per litre. Importantly, “Relevant Athletes” who are females and belong to a specific list of DSD conditions all happen to be XY. These athletes are to reduce their testosterone levels to 5 nml/L for at least six months and thereafter to maintain it at that level for as long as they wish to participate in these races (the 2018 Regulations). They are therefore being asked to lower their testosterone levels to help ensure a level playing ground based on the debatable assumption that testosterone levels impact on athletic performance. These rules were rolled out against the backdrop of existing standards on human rights demanding, among other things, that the rights of all people are respected. That would include athletes. One such right is the right to health.